Analysis of Factors Affecting the Rental Value of Business Space in Jayapura Regency and Jayapura City - Firdaus, M. As'ad (Benefit: Journal of Bussiness, Economics, and Finance, 2024)
This study examines the factors that influence the rental value of business space in Jayapura Regency and Jayapura City. This study aims to understand the relationship between business space specifications and supporting facilities, and their impact on business space rental prices. The analysis conducted using multiple linear regression identified several significant factors that influence rental prices. The results of the study indicate that the area of ​​space and the rental period have a negative effect on rental prices, meaning that the larger the space and the longer the rental period, the lower the rental price per square meter. On the other hand, the presence of facilities such as air conditioning, parking, water, and cleanliness have a positive effect on rental values, with business spaces that have these facilities having higher rental prices. In addition, the designation of the area also has an effect, where commercial areas have higher rental prices compared to office or residential areas. This study uses primary data collected through surveys and interviews with business space owners, tenants, and property managers in the area. This study provides valuable insights for tenants and business space owners to better understand the dynamics of the business space rental market in Jayapura and provides recommendations for optimizing business space rental prices through improving facilities and selecting strategic locations.. Cata Key:Rental Value, , Multiple Linear Regression, Business Space